Involvement of Bachelor of Administrative Science & Policy Studies students' UiTM Sarawak in health and fitness activities / Miza Aliesya Sandra Suhaimi and Nur Nabilah Abdul Hadi - Suhaimi, Miza Aliesya Sandra; Abdul Hadi, Nur Nabilah (2017)
This research study analyse the Involvement in Health and Fitness Activities among Bachelor of Administrative Science & Policy Studies Students’ in UiTM Samarahan. Health and fitness are import aspects of a person’s wellbeing. To enhance health and fitness adequately through physical movement or exercise, we have to see how this comes to fruition. For huge numbers of these progressions, the stimulus has been terribly characterized as far as sort, power, term, and recurrence of activity. Thus, in order to verify the active respondents towards health and fitness activities, this research will determine the level of motivating factors on the respondents which motivation factors are the most influence them to get involve in health and fitness activities and also it will identify the types of health and fitness activities joined by the respondents. In addition, the most importance is how frequent does the respondents involve in health and fitness activities in a week which activity ought to be performed day by day, 3 to 5 times a week, possibly every other day or ought to be supplemented with some overwhelming resistance and flexibility exercises. Besides, it also analyse the factors that inhibit respondents to involve in health and fitness activities. So, by having this research we can see the involvement in health and fitness activities among the respondents.